Ethanol sensor using tapered optical fiber coated with graphene-based nanomaterials - Girei, Saad Hayatu (2014)
Recently, studies based on tapered optical fiber have received much attention as compared to conventional fiber. Tapered optical fiber was found to be more sensitive as compared to the conventional fiber due to the manner of light propagation in the tapered optical fiber core. Combining the tapered fiber with a nanomaterial based sensing layer can produce novel and highly sensitive optical sensor. Graphene and graphene oxide (GO) has emerged as a leading materials in wide variety of applications including chemical sensing due to its exceptional thermal, optical and mechanical properties. Their nanostructures have a huge surface area that enhances the sensor-analyte interaction and thus, improves the sensing performance. However,their potentials as a sensing layer in the optical fiber sensor, system especially using tapered fiber towards volatile organic compounds such as liquid ethanol are yet to be fully explored. Ethanol is used in various industries such as pharmaceutical, food industries and medical. It is also increasingly used as a biofuel to replace the conventional fossil based fuels. In this thesis, ethanol sensors using tapered multimode optical fiber coated with graphene and GO were successfully developed.Tapered optical fibers were fabricated using Vytran glass processing workstation to achieve tapers with different waist diameters. The multimode tapered optical fibers were coated with graphene and graphene oxide as the sensing layer using the drop casting technique. Graphene was produced using sodium dodecyl benzene sulfonate (SDBS) while GO was produced using the simplified Hummers method. Graphene and GO thin films were characterized using scanning electron microscopy (SEM),Raman and ultraviolet-visible (UV-Vis) spectroscopies. The working principle of the optical sensor is based on the absorbance changes upon exposure to various ethanol concentrations in water. Sensing results indicate that the absorbance response changes linearly when the sensor was exposed to ethanol concentrations in the range of 5% to 40% in water. While both tapered optical fiber with and without the sensing layer reacted towards ethanol, the ones coated with graphene and GO showed higher sensitivity and displays high repeatability and reversibility. As compared to the fiber coated with graphene, the ones coated with GO exhibited fast sensing performance by having both response and recovery times of less than 40 s. The GO coated sensor also exhibited higher sensitivity, as much as 0.814/vol% ethanol concentrations, than graphene coated sensor, 0.669/vol% ethanol concentrations. The developed sensors could be a suitable candidate for the practical applications of environmental monitoring and safety requirements in industries.